Strategi Pengelolaan Berkelanjutan Sumber Daya Perikanan untuk Memperkuat Ketahanan Ekonomi Masyarakat Pesisir Indragiri Hilir, Riau: Penelitian - Sintia Nur Afika; Taryono; Suci Lestari; Reva Indah Permata Sari Sitohang; Al Bazari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The coastal community of Indragiri Hilir, Riau, heavily depends on fishery resources as their main livelihood and a pillar of local economic resilience. However, excessive exploitation, degradation of coastal ecosystems, and climate change threaten the sustainability of fishery resources in this region. This study aims to analyze the existing management conditions of fisheries and formulate sustainable management strategies that can strengthen the economic resilience of the coastal community. The research method employs a qualitative and quantitative approach through field surveys, in-depth interviews with fishers and stakeholders, as well as secondary data analysis related to fishery production and the socio-economic conditions of the community. The results indicate that overfishing, mangrove habitat destruction, and weak regulatory enforcement are primary challenges in managing fisheries in Indragiri Hilir. Recommended strategies include the implementation of marine conservation zones, strengthening fisher institutions, diversifying businesses based on sustainable fisheries such as environmentally friendly aquaculture and marine ecotourism, and enhancing community capacity through training and access to capital. Integrating local wisdom with ecosystem-based approaches is key to successful sustainable management. Sustainable fisheries management not only ensures the long-term availability of resources but also improves the income and welfare of coastal communities. This study is expected to serve as a reference for local governments and stakeholders in formulating adaptive and inclusive fishery management policies to achieve resilient and sustainable economic security for coastal communities.